THE USE OF REDUPLICATED ADJECTIVES IN CONTEMPORARY NOVELS - Irene Pabuntang; Aryana N Qarimah (Paratext: International Journal of Language and Literature, 2025)
Reduplication adjectives are widely used in contemporary novels to show beauty. This study aims to determine the use of reduplication adjectives in contemporary novels. The data sources are sentences containing reduplication adjectives in three contemporary novels with the titles "Karena Aku Cinta" by Mita Juniar published by Zettu East Jakarta in 2014, "Kangen" by Putu Deriska published by Euthenia West Jakarta in 2015, and Perahu Kertas by Dewi Lestari published by Bentang Pustaka Yogyakarta in 2012. The method used is the listening method with a note-taking technique. The listening was done by reading the three novels and recording all the reduplication adjectives in the contemporary novels (“Karena Aku cinta” karya Mita Juniar, “Kangen” karya Putu Deriska, dan Perahu Kertas karya Dewi Lestari). The results show that there are two main forms, namely basic reduplication adjectives and affixed reduplication adjectives. The affixed adjectives are divided into five patterns: ber- D+R, se- D+R -nya, D+R -an, ter- D+R, and D+R -nya, which show the process of derivation and inflection as well as word class changes, such as from nouns or numerals to adjectives. In terms of meaning, adjective reduplication contains six types: sungguh-sungguh, walaupun, berulang-ulang, menyerupai, intensitas, dan superlatif.